Critical thickness investigation of magnetic properties in exchange-coupled bilayers - Suarez, Roberto Lazaro Rodriguez (2011)
We present a systematic investigation of the magnetic properties of two series of polycrystalline ferromagneticantiferromagnetic bilayers (FM-AF) of Ni81Fe19(10nm)/Ir20Mn80(tAF) grown by dc magnetron sputtering. One series was grown at an oblique angle of 50◦ and the other one was grown at 0◦. Ferromagnetic resonance (FMR) was used to measure the exchange bias field HE, the rotatable anisotropy field HRA, and the FMR linewidth H as a function of the antiferromagnetic layer thickness tAF. Three relaxation channels due to isotropic Gilbert damping, anisotropic two-magnon scattering, and mosaicity effects are simultaneously distinguished through the angular dependence of the FMR linewidth. In the regime of small IrMn layer thicknesses, not enough to establish the exchange bias anisotropy, the FMR linewidth shows a sharp peak due to the contribution of the two-magnon scattering mechanism. The results presented here are of general importance for understanding the dynamics of magnetization in the FM-AF structures